2021
DOI: 10.1186/s13048-021-00879-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymorphism in various potential genes on polycystic ovary syndrome susceptibility and pathogenesis

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinopathies affecting the early reproductive age in women, whose pathophysiology perplexes many researchers till today. This syndrome is classically categorized by hyperandrogenism and/or hyperandrogenemia, menstrual and ovulatory dysfunction, bulky multi follicular ovaries on Ultrasonography (USG), and metabolic abnormalities such as hyperinsulinemia, dyslipidemia, obesity. The etiopathogenesis of PCOS is not fully elucidated, but it seems that the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 294 publications
0
17
0
Order By: Relevance
“…Other candidate genes have recently been proposed in the literature, including FSHR (follicle-stimulating hormone receptor) [ 86 ], and AR androgen receptor [ 87 ]. Large prospective and randomized trials are needed: (i) to establish gene-based treatemnt guidelines; and (ii) to understand the interplay between different polymorphisms and other environmental/lifestyle factors [ 88 , 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other candidate genes have recently been proposed in the literature, including FSHR (follicle-stimulating hormone receptor) [ 86 ], and AR androgen receptor [ 87 ]. Large prospective and randomized trials are needed: (i) to establish gene-based treatemnt guidelines; and (ii) to understand the interplay between different polymorphisms and other environmental/lifestyle factors [ 88 , 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown the impairment of androgen and ovulation pathways in women with PCOS, resulting in hyperandrogenism and ovulatory dysfunction. Among these biochemical pathways are genes associated with PCOS, including insulin secretion (e.g., INSR , IRS -1, INS ), chronic inflammation (e.g., TNF-α, IL-6), coagulation cascade and complement (e.g., VWF ), signalling (e.g., AMH , LHCGR , INS , ADIPOQ ), cancer (e.g., MMP , AR1 , INS ), and steroidogenesis (e.g., CYP11A1 , CYP17A1 , CYP19A1 ) pathways [ 33 , 34 ].…”
Section: Biochemical Pathways In Pcosmentioning
confidence: 99%
“…Critical genes that encode for steroidogenic enzymes, including cytochrome P450 enzymes (CYP), have also been investigated. In this regard, polymorphisms in CYP11A, CYP17, CYP19 and CYP21 genes are related to the alteration in the steroidogenesis with an overproduction of androgen hormones [ 45 ]. Recent studies have demonstrated that CYP 17 5’-UTR MspA1 (rs743572) and CYP 19 (rs2414096) polymorphisms increase the susceptibility to develop PCOS in young women, altering different hormone genesis pathways [ 46 , 47 , 48 ].…”
Section: Mechanisms Involved In Pcos Pathogenesismentioning
confidence: 99%